An Analysis of the Salient Features of René Hurtubise's Conception of the University - Fiorino, Al (Canadian Journal of Higher Education, 1976)
In recent years an attempt to formulate an "idea of the university" suited to the Canadian scene has been made by René Hurtubise, undoubtedly a key figure in Québec higher edu- cation. An examination of this attempt reveals, what I would consider, a positive tendency in Canadian higher educational research to be more theoretical and philosophical. However, at the same time, it also discloses, as does much of the literature in this field, a lack of self- evaluation, a quality important to the elaboration of a sound and viable educational model.